Souvenir Product Development of Sukhothai Local Sewing and Craft of Khao Kaew Srisomboon Community Enterprise, Sukhothai Province - Rampungjit, Rungrutai; Sorose, Apirat (Area Based Development Research Journal, 2021)
Khao Kaew Srisomboon Local Sewing and Craft Community Enterprise in Thung Saliam district, Sukhothai province has been made up of a group of skilled women in sewing and local fabric arts residing in the subdistrict of Thung Saliam, Sukhothai province. The group produced products in the form of women’s fabric bags and wallets made from cotton blended with synthetic fibers and sold them to local customers in the community or customers who ordered from abroad. Currently, it has been found that the products cannot attract new customers; therefore, the research objective was to create distinctive souvenirs out of Sukhothai woven fabrics by using the cultural community woven fabrics to create new product styles with quality improvement. The processes included 1) the situational analysis of the group members of the sewing and craft community enterprise, 2) the construction of guidelines for product design, 3) product design and product prototyping, 4) product development skills training and product prototyping practice, and 5) establishment of product quality standards to achieve the Community Product Standard Certification. The community itself was also involved in the product design and development process so that the community members obtain knowledge and skills. Three new types of souvenirs were developed including rag dolls, pillows, and office supplies. It has been found that new woven fabric products could be sold at 60% higher than the original, generating a monthly income of about 20,000 baht. The products have also proceeded to attain the community product standard certification under the type of hand-woven-material cushion group called "Handmade Panson” brand. Finally, their distribution channels for the community and interested parties are located at Khao Kaew Si Somboon subdistrict, Thung Saliam district, Sukhothai province, Bumrungrad hospital foundation, public and private trade fairs, and on different social media.